The impact of shared decision-making on quality of life in systemic lupus erythematosus practice: findings from the TRUMP2-SLE prospective cohort study - Hidekawa, Chiharu; Yajima, Nobuyuki; Yoshimi, Ryusuke; Suzuki, Naoki; Yoshioka, Yuji; Sakurai, Natsuki; Oguro, Nao; Shidahara, Kenta; Hayashi, Keigo; Ichikawa, Takanori; Kishida, Dai; Miyawaki, Yoshia; et al. (Frontiers in Immunology, 2026)
ObjectivesShared decision-making (SDM) is increasingly emphasized in the treatment of systemic lupus erythematosus (SLE). Although SDM has been linked to quality of life (QoL) in various diseases, its direct and quantitative relationship with QoL in SLE remains unclear. This study aimed to investigate the longitudinal relationship between SDM and QoL in a multicenter cohort of patients with SLE.MethodsPatients aged 20 years or older diagnosed with SLE according to the 1997 revised American College of Rheumatology criteria were included. The association between baseline scores on the SDM-Q-9, an indicator of SDM, and one-year changes in scores on the LupusPRO, a QoL measure for patients with SLE, was examined using multiple regression analysis. Additionally, we evaluated the association between SDM changes and QoL, both overall and across the four groups, categorized by baseline SDM levels and SDM changes.ResultsA total of 436 patients were included in this analysis. Higher baseline SDM-Q-9 scores were associated with a 0.16-point improvement (95% confidence interval [CI]: 0.071–0.24, p = 0.001) in non-health-related QoL, particularly in the satisfaction with care domain (0.36-point improvement, 95% CI: 0.14–0.58, p = 0.003). For health-related QoL, SDM-Q-9 scores improved the procreation domain by 0.13 points (95% CI: 0.033–0.22, p = 0.01). Longitudinal changes in SDM over one year did not substantially alter these associations.ConclusionsHigher SDM levels in patients with SLE may enhance their QoL. Sustained high SDM appears to be more influential than short-term improvements.